Beyond the Nasca Lines : Ancient Life at La Tiza in the Peruvian Desert - Conlee, Christina A. (Book collections on Project MUSE., 2016)
This book focuses on the site La Tiza, the longest continuously occupied site in the Wari Empire, and therefore provides invaluable insights into the rise and fall of the Wari state.